PROSPEK INDUSTRI KREATIF KERAJINAN PIGURA DI KECAMATAN PEKANBARU KOTA - Amelia, Cindy; Basri, Syafril; Pailis, Eka Armas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research located in Pekanbaru, the goal of this research is to know how prospect of frame creative industry at Pekanbaru kota sub-district. The methodological research is descriptive analysis. That the data type are secondary and primer data, it consists of some aspects are promotion, technical and production, Social economics, and environment. While the quantitative analysis are done to analyze financial aspects such as Net Present Value (NPV), Benefit Cost Ratio (B/C), and Internal Rate of Return (IRR). The research techniques of the data collection are using questioner, interview, and observation. Which is sampling use is census method. Where, the total population is collected. There is 6 unit of frame industry over there collected. The result of the research from frame industry, the frame industry is suitable to develop. Measuring from non financial aspect likes promotion, technique and industry, social economic and environment aspect. While, based on finance proper test criteria, it is proper in NPV mark as frame industry amount Rp.62.079.701,68>0 it means that frame industry is suitable and fulfill the criteria to be operated. And then, (B/C Ratio) shows 1,10 >1, it means that Frame Industry is worth to operate. While, based on calculated of IRR mark shows that 55%>12%. Meaning that frame industry is suitable and fulfill the criteria to be operated.Keywords: Creative frame industry, and business research.